Konsep Dasar Pengukuran Dan Skala Dalam PenelitianManajemen Pendidikan: Kajian Pustaka - Prihaten Maskhuliah; Nazwa Bunga Alzira Rimosan; Indah Maimanah; Dzulfiana Prawati; Nadia Rahmadani; Muflikah Min Khoiratun Nisa (CV. ITTC INDONESIA, 2025)
This research discusses the basic concepts of measurement and scales in the context of educational management. The aim is to help students understand the importance of using valid and reliable measurements in research. Using the literature study method, this article reviews the measurement process which includes the conceptualization and operationalization stages, as well as several important principles such as sensitivity, validity, and reliability. The discussion also covers objects that can be measured, types of scales (nominal, ordinal, interval, and ratio), and forms of scales that are often used, such as Likert scales and Guttman scales. In conclusion, a good understanding of measurement and scales is needed so that decision-making in education management can be based on strong data. Hopefully, this paper can serve as an initial guide for students or novice researchers in developing appropriate and effective research instruments.